Odpowiedzi

Najlepsza Odpowiedź!
2010-03-10T16:58:51+01:00
A) 4x + 6y = 4,80
x + 10y = 4,60|*(-4)

4x+6y=4,80
-4x-40y =-18,4

-34y=-13,6|:(-34)
y=0,4

4x+6*0,4=4,80
4x+2,4=4,80
4x=2,4|:4
x=0,6
y=0,4
x=0,6



b) 6x +7y = 54|*7
7x+6y = 50|*(-6)

42x+49y=378
-42x-36y=-300

13y=78|:13
y=6

7x+6*6=50
7x+36=50
7x=14|:7
x=2

y=6
x=2

2010-03-10T17:32:54+01:00
A) 4x + 6y = 4,8
x + 10y = 4,6

4x + 6y = 4,8
x = 4,6 - 10y

4(4,6 - 10y) + 6y = 4,8
x = 4,6 - 10y

18,4 - 40y + 6y = 4,8
x = 4,6 - 10y

18,4 - 34y = 4,8
x = 4,6 - 10y

18,4 - 4,8 = 34y
x = 4,6 - 10y

34y = 13,6
x = 4,6 - 10y

y = 0,4
x = 4,6 - 10*0,4

x = 0,6
y = 0,4

spr.: 4*0,6 + 6*0,4 = 2,4 + 2,4 = 4,8
0,6 + 10*0,4 = 0,6 + 4 = 4,6


b) 6x + 7y = 54
7x + 6y = 50

7*(6x + 7y) = 54*7
-6*(7x + 6y) = 50*(-6)

42x + 49y = 378
-42x - 36y = -300
+______________

13y = 78
y = 6

6x + 7*6 = 54
y = 6

6x + 42 = 54
y = 6

6x = 12
y = 6

x = 2
y = 6

spr.: 6*2 + 7*6 = 12 + 42 = 54
7*2 + 6*6 = 14 + 36 = 50
1 5 1